2004
DOI: 10.1002/lsm.10248
|View full text |Cite
|
Sign up to set email alerts
|

Infrared imaging of subcutaneous veins

Abstract: Imaging in the near-IR range (880-930 nm) provides relatively good contrast of subcutaneous veins, underscoring its value for diagnosis. This technique has the potential for the diagnosis of varicose veins with a diameter of 0.5-2 mm at a depth of 1-3 mm, guidance of venous access, podiatry, phlebotomy, injection sclerotherapy, and control of laser interstitial therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(61 citation statements)
references
References 28 publications
1
59
0
1
Order By: Relevance
“…While the Red band can reveal some vein structure, the NIR band can show the palm vein structures as well as partial line information. In our system, the palm vein structure acquired in the NIR band is not as clear as that reported in [23], because the CCD in our system is a standard closed-circuit television camera, instead of a NIRsensitive camera, to reduce cost. Moreover, we do not add an infrared filter in front of the CCD because the infrared filter would cut off the visible light and affect the acquisition of clear palmprint images under the visible spectrum.…”
Section: Online Multispectral Palmprint System Designmentioning
confidence: 99%
See 2 more Smart Citations
“…While the Red band can reveal some vein structure, the NIR band can show the palm vein structures as well as partial line information. In our system, the palm vein structure acquired in the NIR band is not as clear as that reported in [23], because the CCD in our system is a standard closed-circuit television camera, instead of a NIRsensitive camera, to reduce cost. Moreover, we do not add an infrared filter in front of the CCD because the infrared filter would cut off the visible light and affect the acquisition of clear palmprint images under the visible spectrum.…”
Section: Online Multispectral Palmprint System Designmentioning
confidence: 99%
“…In the NIR spectrum, an NIR LED array peaking at 880 nm is used. It has been shown that light in the 700-to 1000-nm range can penetrate human skin, whereas 880-930 nm provides a good contrast of subcutaneous veins [23]. Fig.…”
Section: Online Multispectral Palmprint System Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Spatial domain methods are procedures that operate directly on these pixels. Spatial domain processes [13] [14] will be denoted by the expression:…”
Section: Image Enhancementmentioning
confidence: 99%
“…The paper discusses about the existing database developed by the Hong Kong Polytechnic University named as Multispectral Palm print Image database. The images of this database are experimented under proposed method includes two step phases I and II mainly focuses on image enhancement [13], morphological image processing and edge detection algorithm. Each part of their database was named as -xxxx‖.…”
Section: Introductionmentioning
confidence: 99%